Educational apps of Bambam Belajar ABC - Zulkifle, Mohammad Fadhil (Universiti Teknologi MARA, Perak, 2022)
Bambam Belajar ABC is an educational application that developed by ZAIM Studio. Even though this application has launched since 2020, it does not have any marketing strategy. This final year project will help to promote this application to the targeted customers.